Wizard and Wart at sea / story by Janice Lee Smith ; pictures by Paul Meisel. - Smith, Janice Lee, 1949- (I can read book., 1995)
While trying to relax on the beach with his dog Wart, Wizard uses his magic to get rid of pesky seagulls but finds his solution to be just as bad as the original problem.